STATE OF SMALL BUSINESS DEVELOPMENT IN UKRAINE - VASIUTA, Viktoriia; PUTRIA, Anastasiia; PIVOVAROV, Vladislav (Herald of Khmelnytskyi National University. Economic sciences, 2022)
The article examines the current state of development of small business in Ukraine, identifies the main problems that hinder it. The development of small business is a necessary condition for unlocking the economic and innovative potential of the country. Small enterprises are able to resist monopolistic structures, keep a balance between the interests of market participants, create all market segments and make them a variety of products and services. The authors emphasize the need to support the functioning and development of small businesses. The presence of a large number of small enterprises in the country’s economy gives the economic system flexibility, maneuverability, adaptability to a rapidly changing environment and market conditions. The economic space of Ukraine has a powerful potential and has ample opportunities for the development of small businesses and entrepreneurship in general. In Ukraine, freedom of entrepreneurship means a real opportunity for citizens to engage in legal activities. This is enshrined in the Constitution of Ukraine, which guarantees everyone the right to engage in entrepreneurial activities that are not prohibited by law. Modern Ukrainian scientists have studied the general characteristics of the functioning of small businesses in Ukraine in modern conditions. The dynamics of the number, composition and structure of small businesses in Ukraine for 2012–2021 is analyzed. Analysis by type of economic activity showed that such areas of activity as trade and services are in priority. The authors note that in their activities small businesses experience problems associated with the financial component. In 2020, in addition to the existing ones, problems were added that caused quarantine restrictions due to the COVID-19 pandemic. The Government of Ukraine provided support to the business sector. Credit holidays were introduced, tax preferences were provided, and targeted and informational support was provided for small and medium-sized businesses. Small business in Ukraine is forced to overcome a number of macroeconomic obstacles, the main reasons for which are the unstable economic situation in the country. Creating favorable conditions for the development of small business is one of the main ways for the state to get out of the economic crisis in war conditions.